Posthuman Biopolitics
XIII, 187 p. 1 illus.
Keywords: This volume presents the first collection of essays dedicated to the science fiction of microbiologist Joan Slonczewski. Posthuman Biopolitics consolidates the scholarly literature on Slonczewski’s fiction and demonstrates fruitful lines of engagement for the critical, cultural, and theoretical treatment of her characters, plots, and storyworlds. Her novels treat feminism in relation to scientific practice, resistance to domination, pacifism versus militarism, the extension of human rights to nonhuman and posthuman actors, biopolitics and posthuman ethics, and symbiosis and communication across planetary scales. Posthuman Biopolitics explores the breadth and depth of Joan Slonczewski’s vision, uncovering the reflective ethical practice that informs her science fiction.